A partner‐switching system controls activation of mixed‐linkage β‐glucan synthesis by c‐di‐GMP in Sinorhizobium meliloti. (26th April 2019) - Baena, Irene; Pérez‐Mendoza, Daniel; Sauviac, Laurent; Francesch, Kevin; Martín, Marta; Rivilla, Rafael; Bonilla, Ildefonso; Bruand, Claude; Sanjuán, Juan; Lloret, Javier
Summary: Sinorhizobium meliloti synthesizes a linear mixed‐linkage (1 → 3)(1 → 4)‐β‐d ‐glucan (ML β‐glucan, MLG) in response to high levels of cyclic diguanylate (c‐di‐GMP). Two proteins BgsA and BgsB are required for MLG synthesis, BgsA being the glucan synthase which is activated upon c‐di‐GMP binding to its C‐terminal domain. Here we report that the product of bgrR (SMb20447) is a diguanylate cyclase (DGC) that provides c‐di‐GMP for the synthesis of MLG by BgsA. bgrR is the first gene of a hexacistronic bgrRSTUWV operon, likely encoding a partner‐switching regulatory network where BgrR is the final target. Using different approaches, we have determined that the products of genes bgrU (containing a putative PP2C serine phosphatase domain) and bgrW (with predicted kinase effector domain), modulate the phosphorylation status and the activity of the STAS domain protein BgrV. We propose that unphosphorylated BgrV inhibits BgrR DGC activity, perhaps through direct protein–protein interactions as established for other partner switchers. A bgrRSTUWV operon coexists with MLG structural bgsBA genes in many rhizobial genomes but is also present in some MLG non‐producers, suggesting a role of this partner‐switching system in other processes besides MLG biosynthesis.